Analisis Nilai Labour Utilitation Rate Tenaga Kerja pada Pekerjaan Struktur Beton - Adzim, M. Fatkhul; Beatrix, Michella (Politeknik Negeri Lhokseumawe, 2024)
Labor productivity has an important role in the success of a project. A low level of productivity can result in the delay of a job, but if the level of productivity has a high value it has a positive impact on the possibility of a job being postponed. This research aims to analyze the level of labor productivity in the field using the productivity rating approach method. The results of the research are that productivity in the Phase 3 Medical Building project at Siti Khodijah Muhammadiyah Hospital Throughout-Sidoarjo is classified in the effective or satisfactory category. .02 %, and 79.53 %. The average LUR values for column, beam and plate formwork work are 80.15%, 77.69% and 77.39% respectively. The average LUR value of casting work is 80.97%.